Transcriptome analysis of mRNA and miRNA in skeletal muscle indicates an important network for differential Residual Feed Intake in pigs - Jing, Lu; Wu, Hui; Miao, Yuanxin; Cao, Jianhua; Brameld, John M.; Parr, Tim; Zhao, Shuhong (Nature Publishing Group, 2015)
Feed efficiency (FE) can be measured by feed conversion ratio (FCR) or residual feed intake (RFI). In this study, we measured the FE related phenotypes of 236 castrated purebred Yorkshire boars, and selected 10 extreme individuals with high and low RFI for transcriptome analysis. We used RNA-seq analyses to determine the differential expression of genes and miRNAs in skeletal muscle. There were 99 differentially expressed genes identified (q ≤ 0.05). The down-regulated genes were mainly involved in mitochondrial energy metabolism, including FABP3, RCAN, PPARGC1 (PGC-1A), HK2 and PRKAG2. The up-regulated genes were mainly involved in skeletal muscle differentiation and proliferation, including IGF2, PDE7A, CEBPD, PIK3R1 and MYH6. Moreover, 15 differentially expressed miRNAs (|log2FC| ≥ 1, total reads count ≥ 20, p ≤ 0.05) were identified. Among them, miR-136, miR-30e-5p, miR-1, miR-208b, miR-199a, miR-101 and miR-29c were up-regulated, while miR-215, miR-365-5p, miR-486, miR-1271, miR-145, miR-99b, miR-191 and miR-10b were down-regulated in low RFI pigs. We conclude that decreasing mitochondrial energy metabolism, possibly through AMPK - PGC-1A pathways, and increasing muscle growth, through IGF-1/2 and TGF-β signaling pathways, are potential strategies for the improvement of FE in pigs (and possibly other livestock). This study provides new insights into the molecular mechanisms that determine RFI and FE in pigs.